137k views
4 votes
Given h(x) = -x2+3x, find h(5).

User Robby Smet
by
5.0k points

1 Answer

4 votes

Answer:

-10, 40, or 5

Explanation:

There are three ways of looking at this problem.

1.

h(x) = -x^(2) + 3x

When finding h(5), that is like saying that in the case that x = 5, find the value of the given expression,

using that knowledge, we can say

h(5) = -(5)^(2) + 3(5)

simplify

= - (25) + (15)

= -10

2.

h(x) = (-x)^(2) + 3x

Again,

When finding h(5), that is like saying that in the case that x = 5, find the value of the given expression,

using that knowledge, we can say

h(5) = (-5)^(2) + 3(5)

simplify

=25 + 15

= 40

3.

h(x) = -2x + 3x

Again,

When finding h(5), that is like saying that in the case that x = 5, find the value of the given expression,

using that knowledge, we can say

h(5) = -2(5) + 3(5)

simplify

= -10 + 15

= 5

User Htea
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.